The Influence of Leadership Style and Work Discipline on Employee Job Satisfaction at the Department of Personnel and Human Resource Development Bandung Regency - Rahayu, Anik; Dayona, Gurawan; Sudaryo, Yoyo (Green Publisher Indonesia, 2025)
In the era of globalization has changed the way of life of traditional society into a modern society. The lifestyle of modern society generally prefers something that is fast, practical, easy and comfortable. To face this competition, every company must be able to develop and manage its resources such as: material capital and machines and even its human resources. In a company, employees are an important factor for the company, because employees have the ability, energy and creativity needed by the company to achieve its goals. This study aims to analyze